Community Livelihood Shifts in the Face of Mangrove Forest Destruction (Case Study of Salemba Village, Ujung Loe District, Bulukumba Regency) - Ahmad Muhajir; Andi Haris; Muhammad Sabiq; Zakaria (Sangia Research Media and Publishing, 2023)
Community livelihood shifts in the face of mangrove debt destruction, in Salemba village, Ujung Loe district, Bulukumba regency. Resulting in damage to residents' ponds and a shift in livelihoods, social and environmental problems become the main thing as a result of logging. This research uses qualitative methods with descriptive analysis including data collection, data presentation, and conclusion drawing. Data collection was carried out using observation, interview and documentation techniques. The results of this study indicate that the logging of mangrove debt greatly changes the order of society that used to be the social function of mangrove debt goes well and also the absence of mangrove reforestation efforts.